Pengajuan gugatan secara class action. (suatu studi perbandingan & penerapannya di Indonesia) - SUNDARI, E (Univ. Atma Jaya, 2002)
Pengajuan gugatan secara class action. (suatu studi perbandingan & penerapannya .